Training the future entrepreneur. (15th November 2004) - Moro, Davide; Poli, Alberto; Bernardi, Chiara
Can entrepreneurship be taught? How can we design and implement a training course in order to develop and support entrepreneurial attitudes and skills? What are the opportunities offered by an entrepreneurship course within a university programme of studies? What are the constraints in implementing it and how could we assess its effectiveness? These questions lead to an interesting ground of research, in pursuit of an empirical way for entrepreneurship development. This paper aims at presenting a field experience that is an entrepreneurship course designed and implemented at Carlo Cattaneo University (Italy).